Security and Fragility of Tenure of Public Servants within the Legal Framework in Uganda - Kimuraheebwe, John Mary Vianney; Atibuni, Dennis Zami; Manyiraho, Deborah (East African Nature and Science Organization, 2022)
This conceptual paper examines the security and fragility of tenure of public servants in Uganda within the established legal and policy frameworks. The conceptualisation involved a systematic literature review of the 1995 Constitution of the Republic of Uganda, as amended, together with a host of other principal and subsidiary legislation that provides for the security of tenure of public servants in Uganda. Other primary sources such as court cases and secondary sources such as policy documents, relevant articles, and reviews were also reviewed. The paper reveals that despite its strength due to its robustness, the labour law of Uganda has gaps which, in addition to the manner of its coordination and implementation, potentially and actually generates both positive and negative expectations and outcomes for the public officers in relation to their security of tenure at the workplace. In this paper, we argue that a fair implementation of the law guarantees tenure security while unfair implementation of it predisposes the public officers to a fragile and insecure tenure. We also suggest strategies that can be employed to avert tenure fragility and enhance tenure security to foster the socioeconomic transformation of the civil servants and the country as a whole